Designing of Data Management System Development for Resource Sharing Systems - Vishwakarma, Rajendra; Dixit, Mohan; Singh, Priyam (IJRDO - Journal of Business Management, 2016)
The success of the institute lays a lot behind its usage of latest technologies for performing their work as fast as possible. Computers made this possible by its arithmetical and logical capabilities. The present work designed the data management system development for resource sharing systems for school management system.